ANALISA KUALITAS LAYANAN BISNIS MAKANAN DAN MINUMAN DI SURABAYA DITINJAU DARI DERAJAT PEMENUHAN KEPUASAN KONSUMEN - Fransisca Andreani (Jurnal Manajemen Pemasaran, 2010)
Food and beverages industries in Surabaya have grown in the last few years. Businessmen have tried hard to deliver the best service they have to their customers in order to satisfy them. This research is done to find out the service quality of food and beverages industries in Surabaya using a quantitative descriptive approach. Service quality is measured by comparing the actual service with the expected service to find Customer Satisfaction Index (CSI). CSI shows that food and beverages industries in Surabaya have already been able to deliver their best service quality to their customers. Hopefully this research is beneficial for the related industries because it can also serve as their feedback to understand their customers better and improve their service quality when needed.